Amish Christmas joy [large type] - Davids, Patricia (Davids, Patricia. Brides of Amish country, 2014)
One minute, Caleb Mast is an oil-rig roughneck who answers to no one but himself. The next, he's the father of a special-needs child he never knew existed. What kind of home can a man without faith or community provide for an eight-year-old girl? For little Joy's sake, Caleb returns to the Amish community he left behind. Joy bonds with schoolteacher Leah Belier, and Caleb feels hopeful for once. But Leah still blames Caleb for dashing long-ago dreams...